A comparative analysis between next-generation sequencing and conventional culture method to detect empyema-associated microorganisms: A systematic review - Yovi, Indra; Syah, Nur A.; Anggraini, Dewi; Simanjuntak, Arya M.; Hanifah, Zulfa N.; Elliyanti, Aisyah (Narra J, 2024)
Empyema poses a significant global health concern, yet identifying responsible bacteria remains elusive. Recent studies question the efficacy of conventional pleural fluid culture in accurately identifying empyema-causing bacteria. The aim of this study was to compare diagnostic capabilities of next-generation sequencing (NGS) with conventional pleural fluid culture in identifying empyema-causing bacteria. Five databases (Google Scholar, Science Direct, Cochrane, Research Gate, and PubMed) were used to search studies comparing conventional pleural fluid culture with NGS for identifying empyema-causing bacteria using keywords. Positive results identified through conventional pleural fluid culture and NGS were extracted. In addition, bacterial profiles identified by NGS were also documented. Joanna-Briggs Institute (JBI) critical appraisal tool was employed to assess quality of included studies. Descriptive analysis was employed to present outcome of interests. From five databases, three studies, with 354 patients, were included. Findings from three studies showed that NGS outperformed conventional pleural fluid culture in detecting empyema-causing bacteria even in culture-negative samples. Moreover, dominant bacterial profiles identified through NGS included Streptococcus pneumoniae, Staphylococcus aureus, and anaerobic bacteria. In conclusion, NGS outperforms conventional pleural fluid culture in detection empyema-causing bacteria, yet further studies with larger samples and broader bacterial profiles are needed to increase confidence and urgency in its adoption over conventional pleural fluid culture.